Hydrocarbon Yield Structure in the Conversion of Heavy Model Molecules (Quinolin-65) on Fluidized Catalytic Cracking Catalyst - Devard, Alejandra Veronica (2012)
The reactivity of a heavy model molecule (quinolin-65, named Q65, a 2,3,7,8-dibenzopyrene derivative) over two different equilibrium fluidized catalytic cracking catalysts of the conventional and resid types was studied at 550 °C and with reaction times that varied from 5 to 20 s, in a batch fluidized-bed laboratory reactor. Two types of experiments were performed to determine the hydrocarbon products resulting from the conversion of Q65. This compound is solid at room temperature, and a solution of Q65 at 4.6 wt % in toluene and pure toluene were used. Conversions and yields were assessed by means of careful mass balances. The product distributions showed that Q65 produced a wide range of hydrocarbons from C1 to C20. These distributions were different according to the formulations of the catalysts. Olefins were predominant among gases and, neatly, aromatics among liquids. Coke yields were high, exceeding 12 wt %. The characteristics of the catalysts were also revealed through the higher activity and hydrogen-transfer ability of the conventional catalyst and the better coke selectivity of the resid catalyst. It was shown that both the linear alkyl chain and the multi-ring core react.